CLIL in the English as a Foreign Language (EFL) University Class: Incorporating Thematic World maps in Learning (Papeles, 2017)
CLIL (Content Language Integrated Learning) has increasingly gained recognition as a methodology for teaching mainstream courses at Colombian universities to foster the learning of English through academic subjects in the social sciences. This is a report of how overlaying thematic maps to identify correlating data has been used to develop support for essays which focus on social issues. As students overlaid thematic maps to identify the relationship between social indicators, they were able to sustain a thesis for their essay thesis topics through geographic research. Hence, the exercise demonstrated the simultaneous learning process advocated by CLIL as students acquired map skills to support a thesis in an essay.